Mechanisms of pressure-mediated cell death and injury in Escherichia coli: from fundamentals to food applications - Gänzle, Michael; Liu, Yang (Frontiers in Microbiology, 2015)
High hydrostatic pressure is commercially applied to extend the shelf life of foods, and to improve food safety. Current applications operate at ambient temperature and 600 MPa or less. However, bacteria that may resist this pressure level include the pathogens Staphylococcus aureus and strains of Escherichia coli, including shiga-toxin producing E. coli. The resistance of E. coli to pressure is variable between strains and highly dependent on the food matrix. The targeted design of processes for the safe elimination of E. coli thus necessitates deeper insights into mechanisms of interaction and matrix-strain interactions. Cellular targets of high pressure treatment in E. coli include the barrier properties of the outer membrane, the integrity of the cytoplasmic membrane as well as the activity of membrane-bound enzymes, and the integrity of ribosomes. The pressure-induced denaturation of membrane bound enzymes results in generation of reactive oxygen species and subsequent cell death caused by oxidative stress. Remarkably, pressure resistance at the single cell level relates to the disposition of misfolded proteins in inclusion bodies. While the pressure resistance E. coli can be manipulated by over-expression or deletion of (stress) proteins, the mechanisms of pressure resistance in wild type strains is multi-factorial and not fully understood. This review aims to provide an overview on mechanisms of pressure-mediated cell death in E. coli, and the use of this information for optimization of high pressure processing of foods.